2020
DOI: 10.18632/oncotarget.27654
|View full text |Cite
|
Sign up to set email alerts
|

Renal cell tumors convert natural killer cells to a proangiogenic phenotype

Abstract: Natural killer (NK) cells are classically associated with immune surveillance and destruction of tumor cells. Inconsistent with this function, NK cells are found in advanced human tumors including renal cell carcinoma (RCC). NK cells with nonclassical phenotypes (CD56 + CD16 dim/neg ; termed decidua NK (dNK) cells) accumulate at the maternal-fetal interface during embryo implantation. These dNK cells are poorly cytotoxic, proangiogenic, and facilitate placenta development. As similarities between embryo implan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 73 publications
0
21
0
Order By: Relevance
“…Moreover, these NK cells are phenotypically and functionally similar to NK cells infiltrating decidua that are shifted toward non-cytotoxic regulatory functions [ 57 , 65 ] and may play a pro-oncogenic role. It has been shown that NK cells may promote tumor growth and vascularization of trophoblast choriocarcinomas [ 39 ] in non–small-cell lung cancer (NSCLC) and renal cell carcinoma, where NK cells can acquire the decidual-like CD56 bright CD16- phenotype related to proangiogenic functions [ 66 , 67 ]. Our results are in favor of a similar role in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these NK cells are phenotypically and functionally similar to NK cells infiltrating decidua that are shifted toward non-cytotoxic regulatory functions [ 57 , 65 ] and may play a pro-oncogenic role. It has been shown that NK cells may promote tumor growth and vascularization of trophoblast choriocarcinomas [ 39 ] in non–small-cell lung cancer (NSCLC) and renal cell carcinoma, where NK cells can acquire the decidual-like CD56 bright CD16- phenotype related to proangiogenic functions [ 66 , 67 ]. Our results are in favor of a similar role in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…There is mounting evidence that NK cells infiltrate various tumors. For instance, NK cells were shown to infiltrate renal cell carcinoma [ 178 , 179 , 180 , 181 , 182 ], melanoma [ 183 , 184 ], breast cancer [ 185 , 186 , 187 , 188 ], hepatocellular carcinoma [ 189 , 190 , 191 ], lung cancer [ 192 , 193 ], prostate cancer [ 194 ], bladder cancer [ 195 ] and rectal cancer [ 196 ]. Although many studies show the presence of intratumoral CD56+ NK cells, studies have also found that intratumoral NK cell infiltration is very low or nonexistent in glioblastoma [ 197 ], colorectal cancer (CRC) [ 198 ], melanoma [ 199 , 200 ], renal cell carcinoma [ 157 ], hepatocellular carcinoma [ 200 ] and breast cancer [ 200 ].…”
Section: Nk Cells In the Context Of Immunotherapiesmentioning
confidence: 99%
“…There is a unique subset of decidual NK (dNK) cells known to participate in vascularization during embryonic and placental development [ 7 ]. Recently, a similar nurturing activity of NK cells has been described under pathological conditions, predominantly in different types of cancer, which indicates the relevance of NK cells in the development of ADDs [ 8 , 9 , 10 , 11 , 12 , 13 ]. A better understanding of the mechanisms in which NK cells regulate angiogenesis and its disorders may be of therapeutic significance.…”
Section: Introductionmentioning
confidence: 83%
“…TGF-β is the most immunosuppressive cytokine in the TME and its increased expression has been found in many types of tumors [ 94 ]. Elevated levels of this cytokine were also found in the plasma of patients with lung cancer [ 95 ], colorectal cancer (CRC) [ 96 ], and renal cell carcinoma (RCC) [ 12 ]. Various tumor cells, including cancer cells, stromal cells, immune cells, and myeloid-derived suppressor cells (MDSCs) are responsible for the excessive TGF-β production in cancer patients [ 97 ].…”
Section: Modulatory Role Of Tumor Microenvironment (Tme) In Nk Cell Proangiogenic Activitymentioning
confidence: 99%